Synthesis, biocompatibility and gene encapsulation of poly(2-Ethyl 2-Oxazoline)-dioleoyl phosphatidylethanolamine (PEtOx-DOPE) and post-modifications with peptides and fluorescent dye coumarin. Issue 14 (22nd September 2021) - Gulyuz, Sevgi; Bayram, Duygu; Ozkose, Umut Ugur; Bolat, Zeynep Busra; Kocak, Polen; Saka, Ongun Mehmet; Devrim, Burcu; Parlak Khalily, Melek; Telci, Dilek; Sahin, Fikrettin; Özçubukçu, Salih; Sezer, Esma; et al.
Abstract: Liposome surface modifications serve great potential applications of liposomes, for instance, increasing stability, bioactive liposome conjugates, and targeted drug, gene, and image agent delivery. In this study, novel targeted lipopolymers, peptide 18/peptide 563-poly(2-ethyl-2-oxazoline)-dioleoylphosphatidyl-ethanolamine (P18/P563-PEtOx-DOPE), have been demonstrated to be successfully synthesized. The structures of P18/P563-PEtOx-DOPE were confirmed by FT-IR spectroscopy, GPC, and 1 H-NMR. In this strategy, poly(2-ethyl 2-oxazoline)-modified liposomes were firstly constructed with molecular weights of 3, 500 and 5, 800 Da. Then, we chose PEtOx5800 -DOPE because it has been obtained better particle size (88.74 ± 0.6816) according to the DLS results. Then, peptides- and dye-PEtOx lipid-based nanovesicle (LN) were prepared by peptide-18, peptide-563, and 7-mercapto-4-methyl coumarin. Genetic material (pDNA) was encapsulated into the liposomes and evaluated the encapsulation of plasmid DNA with migration by using agarose gel electrophoresis. In vitro cytotoxicity experiment results on prostate cancer and breast cancer cell lines, parallelly with the healthy prostate (PNT1A) and breast (MCF10A) epithelial cell lines, cells showed insignificant toxic effects. Thus, we can suggest a novel PEtOx phospholipid thanks to this article and its integration with ligands, which great potential for gene transfer system. Graphical Abstract: UF0001